The Spiritual Philosophy of Ibn al-'Arabi: Between the Exoteric and Esoteric Dimension - Rozi, Syafwan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The objective of this article is to examine the spiritual philosophy of Ibn al-‘Arabi especially the spiritual stages start from the religious teaching aspects (exoteric) and spiritual (esoteric). The complexity of Ibn al-‘Arabi’s teachings needs to be investigate to respond the accusations from the religious conservative groups that state the practices done by the spiritualists are deviant religious teachings and even are considered as strange behavior and a symptom of mental illness. Through literature study, this research uses descriptive analysis method or content analysis with a normative theological approach to Ibn Arabi's works. The present study first investigated how Ibn al-’Arabi explained the dichotomy between the exoteric and esoteric dimensions and also its impact on the psychology in his spiritual philosophy. The findings of this study showed that the stages of the spiritual such as repentance, asceticism, austerity, ecstasy, clairvoyance, and so on are the transcendental consciousness which cannot be understood using only the esoteric dimension, but also using the obedience toward the exoteric dimension. A true spiritualist such as the saints and the prophets are the spokesman for God on the earth to give the enlightenment of the life in the world.